ANALYZE THE ADVANTAGES AND COSTS OF PROCESSING DIRTY SWALLOW'S NESTS TO FINISHED PRODUCTS USING THE C5.0 ALGORITHM - Pasaribu, Milwan; Irmayani, Decy; Nasution, Fitri Aini (INFOKUM, 2022)
Swallow's nest is a very popular health product nowadays. This can happen due to swallow's nest has many health benefits such as antioxidant, anti-inflammatory, antiaging, anticancer, immune-boosting and accelerating wound healing. However, the production of swallow's nest is difficult to do so that the product of swallow's nest becomes expensive. This study aims to analyze the costs and benefits required to produce swallow nests. The method used is the C5.0 algorithm which uses a decision tree. The results showed that the root node was obtained, namely the drying stage of the swallow's nest. If the costs required at this stage were equivalent to the existing capital, the company would get benefit. Conversely, if the required cost exceeds the existing capital, the company will experience a loss. Through the decision tree, it can be determined that the determinant or root node of the swallow's nest production process is the stage of the swallow's nest drying process. If the capital is within the budget (budget) then the company will generate profits. Meanwhile, if the existing capital is insufficient (pass) then the company will suffer losses. Based on the results of this study, it can be suggested to use the C5.0 algorithm method in analyzing the costs and profits generated from a production process that produces finished products for sale.